2010
DOI: 10.1016/j.wem.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Sailing Injury and Illness: Results of an Online Survey

Abstract: The most common injuries in both keel boats and dinghies are soft-tissue injuries to the extremities. Severe injuries and illnesses in sailing are uncommon in this study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 17 publications
4
61
0
Order By: Relevance
“…This is similar to a previous study from Rhode Island Hospital in 2006 which also reported that lower extremity injuries were the most common in sailors 14. This was also the case in another study from New Zealand on 28 elite Olympic class sailors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to a previous study from Rhode Island Hospital in 2006 which also reported that lower extremity injuries were the most common in sailors 14. This was also the case in another study from New Zealand on 28 elite Olympic class sailors.…”
Section: Discussionsupporting
confidence: 91%
“…A retrospective study reported that the most common complaint was low back pain followed by knee injury 13. Another internet-based, retrospective study, concerning sailing related injuries and illnesses, reported, however, that the most common types of injuries were contusions, lacerations and sprains localised to the lower extremity (44%), upper extremity (38%) and head/neck (12%) 14. During the 2008 Olympic Games, there were three injuries reported among the 400 sailors 15…”
Section: Introductionmentioning
confidence: 99%
“…Most injuries in the Olympic classes were overuse injuries, in keeping with the findings of previous studies 22 33 34. The skiffs, however, reported mainly acute trauma (49er, 39%; 49erFX, 40%), including fractures and dislocations.…”
Section: Discussionsupporting
confidence: 88%
“…The bulk of the cases were reported, again in the 49erFX class, where there were three head injuries (prevalence of 5% within the 49erFX class) and two concussions (prevalence of 3% within the 49erFX class). In Nathanson et al 's22 study, head injuries accounted for 11% of injuries in dinghies, and importantly, concussions made up 25% of all severe injuries. The concussion and head injury data from this study adds to the justification for sailing bodies worldwide to consider mandating the use of helmets, at least for the high-risk sailing classes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation